Effect of natural gums on pasting, rheological, structural and hydrolysis properties of kudzu starch - Xinming Zhang; Ke Zhang; Ning Yang; Yaqian Xiao; Yonghong Peng; Zhigang Han; Wei Su; Guihong Sun; Jun Wang (Current Research in Food Science, 2023)
Hydrocolloids have been widely used to adjust properties of natural starches, but related research on kudzu starch is still rare. In this study, we investigated the effects of gum arabic (AG), sodium alginate (SA), locust bean gum (LG), and guar gum (GG) on kudzu starch from the perspective of its particle size, pasting, texture, rheology, dehydration rate, thermal properties, microstructure, and sensitivity to amyloglucosidase. Results showed that GG significantly increased the particle size of starch. Addition of AG led to lower peak-, final- and holding-viscosity. SA increased the retention viscosity of kudzu starch, while LG and GG increased its peak viscosity. Addition of hydrocolloids increased the hardness, chewiness, and cohesiveness of starch-hydrocolloid complexes, and reduced the dehydration rate of complex gels. Dynamic rheological data showed that the energy storage modulus (G′) was significantly higher than the loss modulus (G″). The magnitude of modulus increased with frequency, and elastic properties were better than viscous properties. Thermal analysis showed that hydrocolloids increased the starting temperature (To), and the final temperature (Tc). With addition of each of these four hydrocolloids, a more regular and porous thick-wall dense structure was formed, which effectively lowered kudzu starch's sensitivity to amyloglucosidase. It indicated that the binding of hydrocolloid to starch may slow down glucose release into blood during digestion. These results will help understand effects of natural hydrocolloid on kudzu starch, as well as expanding its application in food industry.